Sex-associated differences in mitochondrial function in human peripheral blood mononuclear cells (PBMCs) and brain - Silaidos, Carmina; Pilatus, U.; Grewal, Rekha; Matura, S.; Lienerth, B.; Pantel, J.; Eckert, Gunter P.; Justus Liebig University Giessen (My University, 2018)
BACKGROUND: Alzheimer´s disease (AD) is the most common form of dementia, and it affects more women than men. Mitochondrial dysfunction (MD) plays a key role in AD, and it is detectable at an early stage of the degenerative process in peripheral tissues, such as peripheral mononuclear blood cells (PBMCs). However, whether these changes are also reflected in cerebral energy metabolism and whether sex-specific differences in mitochondrial function occur are not clear. Therefore, we estimated the correlation between mitochondrial function in PBMCs and brain energy metabolites and examined sex-specific differences in healthy participants to elucidate these issues.METHODS: The current pilot study included 9 male and 15 female healthy adults (mean age 30.8 +/- 7.1 years). Respiration and activity of mitochondrial respiratory complexes were measured using a Clarke-electrode (Oxygraph-2k system), and adenosine triphosphate (ATP) levels were determined using a bioluminescence-based assay in isolated PBMCs. Citrate synthase activity as a mitochondrial marker was measured using a photometric assay. Concentrations of brain energy metabolites were quantified in the same individuals using (1)H-magnetic resonance spectroscopy (MRS).RESULTS: We detected sex-associated differences in mitochondrial function. Mitochondrial complexes I, I+II, and IV and uncoupled respiration and electron transport system (ETS) capacity in PBMCs isolated from blood samples of females were significantly (p < 0.05; p < 0.01) higher compared to males. ATP levels in the PBMCs of female participants were approximately 10% higher compared to males. Citrate synthase (CS) activity, a marker of mitochondrial content, was significantly (p < 0.05) higher in females compared to males. Sex-associated differences were also found for brain metabolites. The N-acetylaspartate (NAA) concentration was significantly higher in female participants compared to males in targeted regions. This difference was observed in white matter (WM) and an area with a high percentage (> 50%) of gray matter (GM) (p < 0.05; p < 0.01). The effect sizes indicated a strong influence of sex on these parameters. Sex-associated differences were found in PBMCs and brain, but the determined parameters were not significantly correlated.CONCLUSIONS: Our study revealed sex-associated differences in mitochondrial function in healthy participants. The underlying mechanisms must be elucidated in more detail, but our study suggests that mitochondrial function in PBMCs is a feasible surrogate marker to detect differences in mitochondrial function and energy metabolism in humans and it underscores the necessity of sex-specific approaches in therapies that target mitochondrial dysfunction.
Keywords: sex differences; blood cells; MR spectroscopy; mitochondria; mitochondrial respiration; N-acetylaspartate; ddc:610